Carbon Stock Estimates due to Land Cover Changes at Sumber Brantas Sub-Watershed, East Java - Priyadarshini, Rossyda; Hamzah, Amir; Widjajani, Bakti Wisnu (Universitas Sebelas Maret, 2019)
Carbon stock is one of the essential types of ecosystem services that are provided by vegetation. Land use has significant effects both directly and indirectly on vegetation cover and strongly influences the carbon stock within the ecosystem. In this study, we have investigated the effect of land cover changes on the carbon stocks at the sub-watershed of Sumber Brantas, Batu city, East Java. This research was conducted at the Junrejo, Batu and Bumiaji districts of Batu city. Land cover classes were determined from satellite imagery. The carbon stock was measured at plot and landscape level using RaCSA. The results showed that forest conversion into plantation forest (pine, Teak, Albizia chinensis, Anthocephalus cadamba) or agricultural land caused losses of the above-ground C-stock of 50 Mg ha-1, while losses of the underground C-stock were 20 Mg ha-1. Tree biomass contributes about 60% of the C-stock on average, while the understorey and necromass contribute C-stock about 2% and 5%, respectively. Mixed forest has a total C-stock as much as 316.64 Mg ha-1, followed by plantation forest (247.19 Mg ha-1), farmland and scrubland i.e. 51.57 Mg ha-1 and 12 Mg ha-1,respectively. As the consequences of forest conversion into cropland (2008 2012), the Sumber Brantas sub-watershed (139,447 ha) has been lost its C-stock as much as 0.83 Mg ha-1 yr-1, equivalent to 3.04 Mg CO2 ha-1 yr-1. This study showed that C-stock will be maintained by managing and planting woody plant which has high tree biomass.